2023
DOI: 10.1029/2023je007914
|View full text |Cite
|
Sign up to set email alerts
|

Meteors May Masquerade as Lightning in the Atmosphere of Venus

C. H. Blaske,
J. G. O'Rourke,
S. J. Desch
et al.

Abstract: Lightning in the atmosphere of Venus is either ubiquitous, rare, or non‐existent, depending on how one interprets diverse observations. Quantifying when and where, or even if lightning occurs would provide novel information about Venus’s atmospheric dynamics and chemistry. Lightning is also a potential risk to future missions, which could float in the cloud layers (∼50–70 km above the surface) for up to an Earth‐year. Over decades, spacecraft and ground‐based telescopes have searched for lightning at Venus usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 86 publications
2
5
0
Order By: Relevance
“…If these abundances are representative of average Venus atmospheric NO abundances, then NO chemistry will provide the most stringent limit on the concentration of gas phase HCHO produced at the top of the clouds. However, it was suggested that lightning, the only known source of NO in the clouds of Venus, might be absent . The details of the atmospheric chemistry can be found in the SI (SI 1.7).…”
Section: Resultsmentioning
confidence: 99%
“…If these abundances are representative of average Venus atmospheric NO abundances, then NO chemistry will provide the most stringent limit on the concentration of gas phase HCHO produced at the top of the clouds. However, it was suggested that lightning, the only known source of NO in the clouds of Venus, might be absent . The details of the atmospheric chemistry can be found in the SI (SI 1.7).…”
Section: Resultsmentioning
confidence: 99%
“…The existence and occurrence rate of lightning on Venus is hotly debated (e.g., Blaske et al., 2022; Gurnett et al., 2001; Hansell et al., 1995; Ksanfomaliti, 1980; Lorenz, 2018; Russell et al., 2007; Strangeway, 1992). One major piece of evidence used as indication of Venusian lighting are whistler‐mode waves in the ionosphere and induced magnetosphere (e.g., Hart et al., 2022; Russell et al., 2007, 2013; Scarf et al., 1980).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In this pursuit, the study of shock phenomena assumes paramount significance. The examination of shockwaves on Earth and other planetary bodies, such as Venus [110][111][112] and Mars [113][114][115], is essential for elucidating fundamental aspects of impact phenomena, planetary geophysics, and atmospheric dynamics. The utilization of infrasound sensing allows us to study the signatures of shockwaves, thus facilitating a more comprehensive understanding of the underlying physical processes, and characterization of the objects that generate them.…”
Section: Path Forwardmentioning
confidence: 99%